Resveratrol and Diabetes - Vallianou, Natalia G. (SBDR - Society for Biomedical Diabetes Research, 2013)
Resveratrol is a stilbene compound, and a phytoalexin, synthesized by plants in response to stressful stimuli, usually caused by infection. It is abundantly present in red wine, ports and sherries, red grapes, blueberries, peanuts, itadori tea, as well as hops, pistachios, and in grape and cranberry juices. The anti-hyperglycemic effects of resveratrol seem to be the result of an increased action of the glucose transporter in the cytoplasmic membrane. Studies on rats with streptozotocin-induced diabetes have demonstrated that the expression of the insulin-dependent glucose transporter, GLUT4, is increased after resveratrol ingestion. Also, resveratrol enhances adiponectin levels, which could be one of the potential mechanisms by which it improves insulin sensitivity. Another important observation is that resveratrol induces the secretion of the gut incretin hormone, glucagon-like peptide-1. Resveratrol is also reported to activate Sir2 (silent information regulatory 2), a SIRT1 homolog, thus mimicking the benefits of calorie restriction. It produces a wide variety of effects in mammalian cells, including activation of AMP-activated protein kinase, which is involved in some of the same metabolic pathways as SIRT1, which may influence other mechanisms via the involvement of nuclear factor kappa B (NF-κB). In the near future, resveratrol-based therapies with either resveratrol or its analogs that have better bioavailability could be useful in the treatment of diabetes and its complications, either alone or in combination with other anti-diabetic drugs.